Dietary habits and nutrient intake in adolescent girls living in Northern Iran - Bazhan, Marjan; Kalantari, Naser; Houhiar-Rad, Anahita; Alavi-Majd, Hamid; Kalantari, Shiva (Archives of Advances in Biosciences, 2013)
Rapid changes in lifestyle and industrialization of communities have an important effect on food intake pattern of society. Regarding the lack of enough data about dietary habits and nutrient intake of adolescents in our society, this study was performed in a group of adolescent girls in Lahijan, North of Iran. In this cross-sectional study, 400 high school girls aged 14-17 years selected by random stratified sampling. Nutritional data were collected by 24-hour dietary recall, food habits and food frequency questionnaires for all samples. The mean energy intake was 2338±611 kcal/d. The contributions of carbohydrate, protein and fat to the total energy intake were 59.3, 11.9 and 28.8%, respectively. The daily intake of energy obtained from breakfast, lunch, dinner and snacks were 16.3, 23.5, 25.9 and 34.3%, respectively. The mean intakes of vitamin A, vitamin D, calcium, phosphorous and zinc were below the Recommended Daily Allowances. The consumption of fresh vegetables and fruit was generally low. Twelve percent in total did not drink milk at all. Almost all the subjects had a prepared meal, most often in the evening, at least four times a week. Regarding the undesirable food pattern and proportions of nutrient intakes, it is necessary to development means of motivating adolescents to eat nutritionally rich foods, good for health and well-being.